Monetary transmission in Germany: New Perspectives on Financial Constraints and Investment Spending - Ulf von Kalckreuth (Deutsche Bundesbank, 2001)
In order to obtain a better understanding of monetary transmission, this paper assesses the importance of the interest rate and credit channels on business fixed investment in the German manufacturing sector. Our panel of financial statements contains 44,345 observations for 6,408 firms. We uncover a rather solid interest channel. A transitory increase in nominal interest rates by 100 basis points would depress investment demand by almost 4% within the first year. Using our direct measure of creditworthiness, we can also document a balance-sheet channel. Relative to unconstrained firms, financially constrained firms exhibit increased sensitivity to internal funds, and decreased sensitivity to the user cost as well as to market demand. Furthermore, changes in the rating of firms seem to affect investment demand in a way that is consistent with the presence of a balance-sheet channel. Quantitatively, however, this balance-sheet channel seems to be of secondary importance. – – Mit Hinblick auf ein besseres Verständnis der monetären Transmission wird hier die Bedeutung des Zinskanals und des Kreditkanals für die Anlageinvestitionen des Verarbeitenden Gewerbes in Deutschland untersucht. Unser Panel von Jahresabschlüssen enthält 44 345 Beobachtungen aus 6 408 Unternehmen. Es kann ein recht kräftiger Zinskanal isoliert werden. Eine transitorische Erhöhung der Nominalzinsen um 100 Basispunkte könnte die Investitionsnachfrage im Laufe eines Jahres um fast 4% drücken. Mit Hilfe eines direkten Maßes für Kreditwürdigkeit können wir außerdem einen Unternehmensbilanzkanal nachweisen. Im Vergleich zu anderen Firmen weisen finanziell beschränkte Unternehmen eine erhöhte Sensitivität für interne Liquidität auf, sowie eine geringere Reagibilität bezüglich der Kapitalnutzungskosten und der Nachfrage. Weiterhin paßt die Wirkung einer Änderung des Unternehmensratings auf die Investitionsnachfrage zu einem wirksamen Unternehmensbilanzkanal. Jedoch scheint letzterer quantitativ von nachgeordneter Bedeutung zu sein.
Keywords: E5; E2; 330; Monetäre Transmission; Investition; Kapitalnutzungskosten; finanzielle Restriktionen; Kreditkanal; Monetary Transmission; Firm Investment; User Cost; Finance Constraints; Credit Channel; Transmissionsmechanismus; Investition; Verschuldungsrestriktion; Kredit; Schätzung; Deutschland; credit channel; interest rate channel